2022
DOI: 10.1080/22221751.2022.2097479
|View full text |Cite
|
Sign up to set email alerts
|

Combining intramuscular and intranasal homologous prime-boost with a chimpanzee adenovirus-based COVID-19 vaccine elicits potent humoral and cellular immune responses in mice

Abstract: The efficacy of many coronavirus disease 2019 (COVID-19) vaccines has been shown to decrease to varying extents against new severe acute respiratory syndrome coronavirus 2 variants, which are responsible for the continuing COVID-19 pandemic. Combining intramuscular and intranasal vaccination routes is a promising approach for achieving more potent immune responses. We evaluated the immunogenicity of prime-boost protocols with a chimpanzee adenovirus serotype 68 vector-based vaccine, ChAdTS-S, administered via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
(37 reference statements)
2
13
0
Order By: Relevance
“…However, the proportions of memory B cells and neutralising antibodies were Meanwhile, all vaccination groups induced a Th1-biased cellular immune response, with higher concentrations of Th1-secreted TNF-a, IL-2 and IFN-g in the five intramuscular-only vaccination groups than those in the intranasal vaccination and homologous prime-boost groups. These findings were consistent with our previous results (44).…”
Section: Discussionsupporting
confidence: 94%
“…However, the proportions of memory B cells and neutralising antibodies were Meanwhile, all vaccination groups induced a Th1-biased cellular immune response, with higher concentrations of Th1-secreted TNF-a, IL-2 and IFN-g in the five intramuscular-only vaccination groups than those in the intranasal vaccination and homologous prime-boost groups. These findings were consistent with our previous results (44).…”
Section: Discussionsupporting
confidence: 94%
“…T-cell response plays an important protective role against HSV-2 infection [ 25 ]. Here, all adenovirus vaccination groups induced Th1 type T-cell response after two immunizations, similar to recent studies [ 47 , 48 ]. The combination-expressed group (rAd-gD2 + rAd-ΔUL25) induced a significantly higher level of the Th1-type immune response, indicating the enhancing effect of rAd-ΔUL25 in inducing a cellular immune response.…”
Section: Discussionsupporting
confidence: 90%
“…Two limitations of this study were T-cell immunity and SARS-CoV-2 challenge, which were not performed to test the cellular immunity and to assess the protection efficiency of booster vaccination. However, various studies have reported previously that T-cell immunity was activated after a booster [23, 35, 46, 47]. Homologous and heterologous boosters in health care workers who had received a priming dose of Ad26.COV2.S Covid-19 vaccine resulted in higher levels of T-cell responses than non-booster group, although T-cell response was significantly larger with mRNA-based vaccines (91%) than with the homologous booster (72%) [23].…”
Section: Discussionmentioning
confidence: 99%